Ultrasonic treatment and synthesis of sugar alcohol modified Na+-montmorillonite clay - Chaudhary, Deeptangshu; Liu, Huihua (Elsevier BV, 2013)
Na+-montmorillonite clay (generally referred to as MMT) is very useful for reinforcing polymeric matrix at very low concentrations (typically, 2–5% wt). These clay particles are typically exfoliated before they can demonstrate the significant gains in heat deflection temperature, modulus, and elongation properties. In the case of hydrophilic biopolymer based matrices, such as carbohydrates and chitosan, exfoliating these nanoclay particles needs greater attention because the exfoliation is typically carried out using hydrophobic oligomers through ion-exchange. This study reports a new method of synthesizing completely hydrophilic MMT-assemblages using hydrophilic plasticizers for biopolymers. We used sugar alcohols (glycerol, xylitol with 3 and 5 hydroxyl groups) and polysaccharide maltodextrin to exfoliate the MMT. Sonication was conducted for MMT nanoclay and plasticizers at different weight ratios. It was confirmed that all plasticizer/modifier led to expansion of MMT gallery spacing (d-spacing) and the change in d-spacing could be related to the molecular structure of the plasticizer. Meanwhile, the extent of exfoliation was maximum with maltodextrin (fully exfoliation with 1:10 and 1:20 ratio of MMT:plasticizer) across all test samples and interestingly, glycerol and xylitol samples quickly established within the MMT galleries and exhibited minimal influence with further increase in relative concentrations.